2023
DOI: 10.1155/2023/6854131
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Family Doctor Contract Services Policy and Perceived Participation in Primary Health Care among Chronic Disease Patients in China: The Mediating Role of the Patient Trust

Abstract: Participation by patients with chronic diseases under primary health care requires more attention to achieve effective disease management and better health outcomes. In 2016, China proposed accelerating the establishment of a system of family doctors (FDs) and strengthening doctor-patient communication to better meet residents’ health service needs. This study aimed to describe perceived participation in primary health care among patients with chronic diseases in northeastern China and explore the impact of FD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 87 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…In addition, several studies have indicated that compared with the reference group of patients without a family physician, hypertensive patients who receive care from their own contracted family physicians have a higher BP control rate [31]. Te family physician contract services policy also appeared to infuence the perceived participation of patients in their healthcare [32]. Healthcare utilization is the quantifcation of services utilized by individuals for the purpose of maintaining health and well-being, preventing and treating health problems, or obtaining information about one's health status and prognosis [33].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have indicated that compared with the reference group of patients without a family physician, hypertensive patients who receive care from their own contracted family physicians have a higher BP control rate [31]. Te family physician contract services policy also appeared to infuence the perceived participation of patients in their healthcare [32]. Healthcare utilization is the quantifcation of services utilized by individuals for the purpose of maintaining health and well-being, preventing and treating health problems, or obtaining information about one's health status and prognosis [33].…”
Section: Introductionmentioning
confidence: 99%